Maximize the Impacts of Forgiveness Education with Moral Agency Development - Lai Yung Wong (Education Sciences)
Forgiveness education is more than the teaching of forgiveness. Since forgiveness education cultivates virtuous characters and the best self as the moral self, it sets the foundation for moral agency development. Based on a review of research and the literature about the psychological processes of forgiveness and moral agency, this article illustrates how the forgiveness virtue and moral agency operate and enhance each other for their common roots in the moral self. Due to their symbiotic relationship, promoting moral agency development in forgiveness education is beneficial for the cultivation of mature forgivers, mature moral agents, and good citizens with virtuous characters. To maximize the effectiveness and the impacts of forgiveness education, the GMIRA method is proposed, which involves setting the learning goal of living and being the best self, social modeling towards the goal, and blending the holistic moral agency concept into the existing forgiveness curriculum using the IRA (invitation, reflection, and assessment) strategies. Since moral agency is adaptive, the IRA methods can be flexibly applied to fit individual developmental needs across time and social-cultural contexts in all types of education. This novel idea is open for future research.